2005
DOI: 10.1002/j.1939-4640.2005.tb01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Could Sperm Aneuploidy Rate Determination Be Used as a Predictive Test Before Intracytoplasmic Sperm Injection?

Abstract: Chromosome abnormalities in embryos are a major cause of implantation and development failures. Some couples with normal karyotypes have repeated implantation failures after intracytoplasmic sperm injection (ICSI). In order to value patients at risk for genetic ICSI failures and the validity of sperm aneuploidy analysis, we have studied cytogenetic abnormalities in sperm from ICSI patients. Twenty-nine patients with normal karyotypes were included. Ten patients had at least 4 ICSI treatments without pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
3
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 23 publications
0
26
3
3
Order By: Relevance
“…No difference was found between men with or without implantation failure (groups 2 and 3). This result differed from a previous study [19] reporting an increased spermatozoa aneuploidy rate for recurrent implantation failure patients compared with patients who received successful IVF for male indication. It should be noted that in the previous study, only ten patients were studied for each group and sperm characteristics differed, with a two fold decrease of sperm count and mobility.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…No difference was found between men with or without implantation failure (groups 2 and 3). This result differed from a previous study [19] reporting an increased spermatozoa aneuploidy rate for recurrent implantation failure patients compared with patients who received successful IVF for male indication. It should be noted that in the previous study, only ten patients were studied for each group and sperm characteristics differed, with a two fold decrease of sperm count and mobility.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies separately reported spermatozoa [19,20], polar body [4] or embryo aneuploidy rate evaluations [9,27,28]. This study is the first to deal with both spermatozoa and oocyte aneuploidy rates in couples with recurrent implantation failure.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Different genomic anomalies are quite frequent in some types of infertility, leading to various spermatogenic abnormalities, and this increases the risk for the offspring and the outcome of infertility treatment (11,22). Diagnostics of the genomic and chromosome anomalies, especially microstructural aberrations, can diminuish the bad consequences, as well as the overwhelming financial and emotional costs of repeatedly unsuccessful iVF procedures (31).…”
Section: Introductionmentioning
confidence: 99%